PENGARUH MODEL TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA WORDWALL TERHADAP KOMUNIKASI MATEMATIS SISWA SEKOLAH DASAR - Nita Andini; Erni Nurjanah; Dewi Fitriani; Fathir Arrahmi; Nurhasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematical communication is one of the important competencies in learning mathematics. Observations at SDN Mandalasari show that the mathematical communication of fifth-grade students is still low because learning is still teacher-centered and the use of interactive learning media is not yet optimal. This study aims to analyze the effect of the Teams Games Tournament (TGT) cooperative learning model assisted by Wordwall media on elementary school students' mathematical communication skills in the topic of fraction multiplication. This study uses a quantitative approach with a quasi-experiment method and a Nonequivalent Control Group Design. The research population consisted of 63 fifth-grade students, including 31 students in the control class (VA) and 32 students in the experimental class (VB), using a saturated sampling technique. Data were collected through essay test instruments (pretest and posttest), then analyzed using descriptive statistical analysis, normality test, and homogeneity test, Independent Samples t-Test, and effect size (Cohen's d). The analysis results showed a significance value (Sig. 2-tailed) of 0.000 (< 0.05), proving that there is a significant effect of the TGT model assisted by Wordwall on students' mathematical communication. The average posttest score of the experimental class (87.81) was significantly higher than that of the control class (78.23). The effect size test produced a Cohen's d value of 1.329, which falls into the large effect category. Therefore, implementing the TGT model assisted by Wordwall media greatly contributes to improving elementary school students' mathematical communication skills.